2014
DOI: 10.2478/bvip-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dirofilaria repens in dogs in central-eastern Poland and histopathological changes caused by this infection

Abstract: The aim of the study was to determine the prevalence of canine dirofilariosis in four provinces of central-eastern Poland and to describe pathological changes occurring during the course of this parasitosis. A total of 188 dogs aged from one and a half up to 16 years were examined for dirofilariosis. Blood samples were analysed for the presence of microfilariae using Knott method, as well as the method of Kingston and Morton. Pathomorphological examination of two dogs was also performed. Histological sections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…This is generally in agreement with the results of a previous study on 1588 dogs from Poland, reporting a much lower prevalence of D. repens in dogs from northern, western and southern Poland, spanning a range of just 0–10 % [10, 21]. Demiaszkiewicz et al [10] reported higher prevalence in dogs from eastern Poland, ranging between 13–16 % for Podlaskie and Lubelskie voivodeships, in regions not included in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is generally in agreement with the results of a previous study on 1588 dogs from Poland, reporting a much lower prevalence of D. repens in dogs from northern, western and southern Poland, spanning a range of just 0–10 % [10, 21]. Demiaszkiewicz et al [10] reported higher prevalence in dogs from eastern Poland, ranging between 13–16 % for Podlaskie and Lubelskie voivodeships, in regions not included in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The presence of adult D. repens in dogs causes canine subcutaneous dirofilariosis, with a range of dermatological manifestations [ 20 ], but apparently may also be asymptomatic and chronic for several years [ 2 , 8 , 19 ]. The pathogenicity associated with accumulating high numbers of microfilariae in the circulating blood of infected dogs is also not well recognized but there are a few reports on possible acute and fatal outcomes of such infections associated with the presence of microfilariae in vital organs (heart, liver, kidney) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although not being highly liver specific ( 21 ), ALP is a marker having a good sensitivity for liver diseases in dogs, suggesting cholestasic disease or chronic hepatitis/cirrhosis. Other parameters suggesting liver injuries, as ALT and AST were reported to be increased in case reports of dogs infected with D. repens ( 5 , 22 ) and in some dogs in our study. This difference, however, was not statistically significant while comparing the infected and uninfected group, suggesting a rather big variability between infected individuals.…”
Section: Discussionsupporting
confidence: 63%
“…In all the cases mentioned, it was confirmed that the infections were caused by the D. repens species. Based on the above data, it can be concluded that currently, the infection of Dirofilaria repens occurs endemically in the Mazowieckie voivodeship, as confirmed by Osinska et al (2014). They also showed numerous cases in dogs from eastern Poland, i.e., the Lublin and Podlasie voivodeships.…”
Section: Resultsmentioning
confidence: 52%